Extraction and Purification of Indole aectic acid from locale isolate Fusarium oxysporum(F2) (Baghdad Science Journal, 2008)
Indole acetic acid (IAA) produced from F. oxysporum (F2) was purified by several steps included extraction by cold ethyl acetate ; Column chromatography using silica gel and TLC chromatography .The pure indole acetic acid (IAA) which produce by F. oxysporum (IAA) was tested by ultraviolet spectra at (200-300)nm ; and appear that the maximum absorbance at 229nm , the high performance liquid chromatography (HPLC) used to test the purity of the indole acetic acid and the results showed one peak at appearance time 3.822 min